2019
DOI: 10.1097/shk.0000000000001163
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Alcohol Ingestion Worsens Survival and Alters Gut Epithelial Apoptosis and CD8+ T Cell Function After Pseudomonas Aeruginosa Pneumonia-Induced Sepsis

Abstract: Mortality is higher in septic patients with a history of alcohol use disorder than in septic patients without a history of chronic alcohol usage. We have previously described a model of chronic alcohol ingestion followed by sepsis from cecal ligation and puncture in which alcohol-fed septic mice have higher mortality than water-fed septic mice, associated with altered gut integrity and increased production of TNF and IFNγ by splenic CD4 T cells without alterations in CD8 T cell function. The purpose of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Early studies determined that exposure of ethanol to the human colonic Caco-2 cell line triggered apoptosis in these epithelial cells [ 128 ]. Although a mouse model of chronic ethanol exposure alone displayed no significant changes in apoptotic protein markers or intestinal permeability in the jejunum [ 129 ], binge alcohol exposure elevated endotoxin levels in rodent models, pointing to the development of a leaky gut in these animals [ 130 , 131 ]. The effects of binge alcohol exposure on time- and dose-dependent gut permeability change, elevated endotoxemia, and fatty liver injury were confirmed by other laboratories [ 121 , 132 , 133 ].…”
Section: The Mechanisms Of Alcohol-mediated Gut Dysbiosis Intestimentioning
confidence: 99%
“…Early studies determined that exposure of ethanol to the human colonic Caco-2 cell line triggered apoptosis in these epithelial cells [ 128 ]. Although a mouse model of chronic ethanol exposure alone displayed no significant changes in apoptotic protein markers or intestinal permeability in the jejunum [ 129 ], binge alcohol exposure elevated endotoxin levels in rodent models, pointing to the development of a leaky gut in these animals [ 130 , 131 ]. The effects of binge alcohol exposure on time- and dose-dependent gut permeability change, elevated endotoxemia, and fatty liver injury were confirmed by other laboratories [ 121 , 132 , 133 ].…”
Section: The Mechanisms Of Alcohol-mediated Gut Dysbiosis Intestimentioning
confidence: 99%
“…This induces an increase of apoptosis and decrease of proliferation of small bowel mucosal cells, leading to the thinning of gut mucosa [ 29 ]. The resulting gut damage is exacerbated in the presence of chronic comorbidities such as cancer and chronic alcohol abuse [ 30 , 31 ]. Such injuries result in the impairment of the gut barrier and dysregulation of intestinal microbiota [ 32 , 33 ].…”
Section: Pathophysiology Of Gut Injurymentioning
confidence: 99%
“…Pneumonia is often accompanied by lung injury [ 12 , 13 ], which turns into pulmonary edema and neutrophil accumulation [ 14 , 15 ]. Zhang et al [ 16 ] found that lncRNA FOXD3-AS1 was the most significantly upregulated lncRNAs in hyperoxia-induced acute lung injury model.…”
Section: Introductionmentioning
confidence: 99%